The determination of the influence of physical workload on the speed of choice reaction among fencers during a fencing combat - Teteris, L. E.; Saulite, S.; Licis, R. (LASE Journal of Sport Science, 2024)
Fencing sport is fast, athletic, and psychologically very sophisticated. In combat sports, it is necessary to react as fast as possible, because combat tactics includes performing attacking and defensive moves during the entire combat. Reaction time, which is one of the factors determining speed, became one of the main athletic input factors for achievement in fencing. Experience gained in other countries shows that physical load has influence on the manifestations of fencers` reaction speed. In other countries, the impact of physical load on fencers` reaction speed was studied using laboratory tests rather than in real environments. The aim of this study is to determine fencers` choice reaction speed under varying intensity loads in real fencing combat circumstances. Research methods: 8 male national foil fencing teams subjects 17-27-year-old participated in the study; the subjects fenced in 16 combats until 5 points and in 16 combats until 15 points, with 32 combats being recorded, and the speed of choice reaction was analysed using a previously developed protocol, using heart rate monitoring to determine heart rate frequency in both subjects during the combat. Analysing the results of the study, it can be concluded that workload intensity influence reaction speed. Both fencers showed decrease in reaction speed in the 3rd and 4th HR zones. The impact of fatigue is significant for reaction stability, therefore a better-trained athlete with a higher level of aerobic and anaerobic training will be able to react more sustainably during fencing combats, facilitating the production of better results.